Recent SDGs and ESG implementation by Qatar - Mohd Thas Thaker, Hassanudin; Sakti, Muhammad Rizky Prima; Qoyum, Abdul; Mohd Thas Thaker, Mohamed Asmy; Hosen, Mosharrof (World Scientific Publishing Co Pte Ltd, 2023)
The gas-rich nation, Qatar, became the first Middle Eastern country to host the FIFA World Cup in 2022, after beating South Korea, Japan, Australia, and the US. Qatar invested an enormous amount of money in implementing the measures outlined by FIFA and United Nation’s Sustainable Development Goals (SDGs), and the World Cup was included in Qatar’s sustainable Vision 2030. Qatar has gained international support and wants to host more mega-events despite controversies surrounding its FIFA World Cup, including workers’ deaths during infrastructure construction and protests from western athletes, politicians, and media against the Qatari government and FIFA’s ban on LGBT+ symbols and alcohol in the stadium. Qatar’s 2022 FIFA World Cup left a sustainable legacy by following ESG principles. This paper analysed how FIFA 2022 applies SDGs, ESG, and Islamic principles and their managerial implications. We concluded with lessons to be learnt from FIFA 2022 and Qatar’s investments in green infrastructure, sustainable mobility, and carbon offsetting, as well as how the country’s efforts to leave a sustainable legacy after the event could inspire other nations.